Contradictions in the evolution of the CAP - Moreno Mozo, Fernando (Przegląd Prawa Rolnego, 2023)
The subject of this article is contradictions in the evolution of the Common Agricultural Policy. The considerations aim to identify these contradictions and their negative consequences. Starting from the peculiarities of the demand for agricultural produce, the author discusses the importance of the Common Agricultural Policy and presents six successive phases of its development. He concludes with a synthesis of the contradictions of the CAP evolution and their negative consequences. He also raises a question as to whether it would be possible to subject commercial activity in agriculture, like in other sectors of the economy, to free competition among a group of states or globally, on the assumption that such competition would be reciprocal and subject to the same standards of quality and food safety.